Intratunical injection of stromal vascular fraction prevents fibrosis in a rat model of Peyronie's disease. (2nd June 2019) - Castiglione, Fabio; Hedlund, Petter; Weyne, Emmanuel; Hakim, Lukman; Montorsi, Francesco; Salonia, Andrea; Bivalacqua, Trinity J.; De Ridder, Dirk; Milenkovic, Uros; Ralph, David; Garaffa, Giulio; Muneer, Asif; et al.
Abstract : Objective: To investigate whether local injection of autologous adipose stromal vascular fraction (SVF) can prevent the development of fibrosis and elastosis in the tunica albuginea (TA) using a rat model of the acute phase of Peyronie's disease (PD). Methods: A total of 24 male 12‐week‐old Sprague–Dawley rats were divided into three equal groups: sham; PD without treatment (transforming growth factor‐β [TGF ‐β]); and PD treated with SVF 1 day after disease induction. Sham rats received two injections of vehicle into the TA 1 day apart. TGF ‐β rats received TGF‐ β1 injection and injection of vehicle 1 day later. SVF rats received TGF‐β1 injection, followed by SVF 1 day later. One month after treatment, all rats underwent measurement of intracavernosal pressure and mean arterial pressure during electrostimulation of the cavernous nerve. The rats were then killed and penises were harvested for histology and Western blot analysis. Results: Erectile function was moderately reduced in the TGF‐β group and was significantly improved after SVF treatment ( P < 0.05). PD rats developed areas of fibrosis with a significant upregulation of collagen III, collagen I and elastin protein expression. These fibrotic changes were prevented when treated with SVF. Conclusions: Local injection of SVF may represent treatment for the acute phase of PD.